Ergonomic analysis applied in aquaculture - Soares, Evandro Bezerra (2023)
Aquaculture plays a very important role in the current Brazilian scenario, helping the income of small families. This activity is considerably new and does not have a specific methodology developed for the fishing activity. Due to these factors, this ergonomic analysis at work (AET) study was carried out, with the purpose of identifying the causes of complaints of body pain and fatigue caused by this activity. For this analysis, the Ergolândia software was used, which is composed of several ergonomic methods. The method used in unloading was the National Institute for Occupational Safety and Health (NIOSH), which deals more specifically with lifting and transporting loads, which analyzes the weight of the load, position of hands and feet, inclination of the trunk, height of the load is raised. Collected data and images were also used as assistance. After carrying out the analyzes and verifying that at all stages the Lifting Index (IL) is above the recommended level, some improvement proposals were made to alleviate or eliminate these employee posture problems. All methodologies identified risk levels that require immediate or short-term ergonomic intervention, aiming to guarantee the safety and health of workers who carry out such activity. The implementation of measures designed to eliminate or minimize risk may involve the allocation of significant human and material resources, increasingly necessary for efficient management. Considering the complexity and variability of the tasks developed, it is recommended that such a decision be preceded by a new study using more precise risk assessment methodologies.